Analysis of the Effectiveness of the Marine Growth Prevention System (MGPS) in Preventing Marine Organism Growth in the Engine Cooling System of MV Ever Clear - Brian Pratama Timur; Monika Retno Gunarti; Nasri; Intan Sianturi; Elly Kusumawati (Journal of Engineering Science and Technology Management (JES-TM), 2026)
The ship engine cooling system is critical for maintaining the operational stability of main and auxiliary machinery. However, biofouling within sea chests and seawater pipelines remains a prevalent issue, leading to flow obstruction, reduced heat transfer efficiency, and potential engine malfunction. While the Marine Growth Prevention System (MGPS) is designed to mitigate this via electrolysis, marine growth persisted on MV Ever Clear, indicating suboptimal system performance. This study aims to analyze the effectiveness of the MGPS in preventing biofouling and to identify factors contributing to its performance degradation. Using a qualitative descriptive method with a case study approach, data were collected through direct onboard observation, interviews with the engineering crew, and document analysis. Results indicate that the decreased effectiveness was primarily caused by insufficient electrode maintenance, unstable electrical parameters (current and voltage), and inadequate operational monitoring. These deficiencies compromised the electrolysis process, preventing sufficient ion release. It is concluded that MGPS efficacy is contingent upon stable electrical parameters, rigorous preventive maintenance, and consistent operational supervision in accordance with established procedures.